Pengaruh Kepemimpinan Transformasional terhadap Tata Kelola SDM Unggul dalam Mendukung Keberlanjutan Perguruan Tinggi Swasta: Studi Kasus di STIA Cimahi - Alimuddin, Alimuddin; Melawati, Fitri (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to analyze the role of transformational leadership in building excellent human resource governance to support the sustainability of private higher education institutions. The research employed a qualitative approach with a case study design at the School of Administrative Sciences (STIA) Cimahi. Data were collected through in-depth interviews, observations, and institutional document analysis, and analyzed using data reduction, data display, and conclusion drawing techniques. The findings indicate that transformational leadership implemented through idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration effectively strengthens strategic human resource governance. The transformation of HR governance is reflected in competency-based recruitment systems, transparent performance evaluation, continuous professional development, and the formation of a collaborative work culture. This strengthened HR governance contributes to improving academic quality, student satisfaction, institutional reputation, and organizational sustainability. However, challenges were identified, including limited financial resources, resistance to change, and suboptimal reward systems. These findings suggest that the success of transformational leadership in private higher education requires consistent structural and organizational cultural support. The success of transformational leadership in private universities requires consistent structural support and organizational culture.